Saving Europe? The unpleasant arithmetic of fiscal austerity in integrated economies - Enrique G. Mendoza; Linda L. Tesar; Jing Zhang (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
Europe's debt crisis casts doubt on the effectiveness of fiscal austerity in highly-integrated economies. Closed-economy models overestimate its effectiveness, because they underestimate tax-base elasticities and ignore cross-country tax externalities. In contrast, we study tax responses to debt shocks in a two-country model with endogenous utilization that captures those externalities and matches the capital-tax-base elasticity. Quantitative results show that unilateral capital tax hikes cannot restore fiscal solvency in Europe, and have large negative (positive) effects at "home" ("abroad"). Restoring solvency via either Nash competition or Cooperation reduces (increases) capital (labor) taxes significantly, and leaves countries with larger debt shocks preferring autarky.
urn:nbn:de:hebis:30:3-361397
Keywords: E61; E62; E66; F34; F42; F62; 330; European debt crisis; capacity utilization; fiscal austerity; tax competition